1989
DOI: 10.1002/j.1875-9114.1989.tb04131.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Inhaled Beclomethasone in Chronic Obstructive Airway Disease

Abstract: The objective of this study was to examine the effectiveness of inhaled beclomethasone in the treatment of stable chronic obstructive airway disease (COAD). Eight patients completed a randomized, double-blind, placebo-controlled, crossover trial of inhaled beclomethasone and oral prednisone. Each patient received 3 treatment regimens given for 14 days: inhaled beclomethasone, prednisone, and placebo. There were no statistically significant differences in pulmonary function tests, oxygen cost diagram, or 12-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Early studies have suggested that there are no benefits of short term inhaled corticosteroids (2)(3)(4)(5)(6)(7)(8). However, many of these studies had a limited sample size.…”
Section: Short Term Clinical Studiesmentioning
confidence: 99%
“…Early studies have suggested that there are no benefits of short term inhaled corticosteroids (2)(3)(4)(5)(6)(7)(8). However, many of these studies had a limited sample size.…”
Section: Short Term Clinical Studiesmentioning
confidence: 99%
“…In the few studies where patients with COPD have been selected according to a significant response to oral corticosteroids, 2 3 the proportion of patients and the size of the eVect have been consistently less in patients receiving inhaled corticosteroids than in those receiving oral corticosteroids. In other studies [4][5][6][7][8][9][10][11] carried out in patients not previously selected for their response to oral corticosteroids, the results have been conflicting with regard to the physiological or functional eYcacy of an inhaled corticosteroid. Some studies have included patients with asthma 10 or younger patients with preclinical COPD.…”
mentioning
confidence: 99%